STRATEGI PENGEMBANGAN PRODUK UNGGULAN YANG BERBASIS OVOP - Juhari Juhari (LPPM STIE PERTIBA Pangkalpinang, 2019)
This study aims to analyze superior products based on OVOP in Cengkong Abang Village, Petaling Village, Petaling Banjar Village, Kemuja Village and Air Duren Village, Mendo Barat District, Bangka Regency, Bangka Belitung Islands Province. This research method was conducted with an evaluation method with a qualitative approach using SWOT analysis to find a formulation of business management strategies for products based on superior One Village One Product (OVOP) for each potential village to be developed. So that each village in Bangka Regency has the characteristics of superior products that will continue to be fostered by the village government, local government and the central government. The superior products developed based on OVOP are expected to be able to enter regional, domestic and international markets